ECONOMIC ACTIVATION OF HUMAN RESOURCES IN TOURISM - Southern Backa district example - - Gajić, Tamara; Đurica, Nina; Bošković, Tatjana (Economics of Agriculture, 2010)
The new age creates the possibility that the social, material and spiritual living conditions needs of all people are developing optimally by their quantity and quality. A wide spread theoretical opinion is that tourism activity already has a special treatment, because as a necessary and generally segment of a life of contemporary man it is considered as a factor of development of the entire economy and society. Unfavorable economic trends in the last years of the twentieth century affected the tourist economy of Serbia, which after years of relative success experienced a decline. This paper, in a concise way, emphasizes the importance of tourism in the process of stimulating or activating the working age population of the Southern Backa District. Among other things, the aim is to highlight the fact that tourism is an economic sector, that will contribute faster growth of entire country economy.